Prevalence and determinants of hypertension unawareness in Egyptian adults: a cross-sectional study of data from the 2015 Egyptian Health Issues Study - Saeed S Soliman, MD, FRCGP; Emily H Guseman, MD; Zelalem T Haile, MD; Gillian H Ice, MD (Elsevier, 2020)
Background: Hypertension is a major risk factor for cardiovascular disease that affects 1·3 billion people and accounts for 17·9 million deaths worldwide annually. Most deaths from hypertension (around 75%) are in low-income and middle-income countries where hypertension prevalence is higher but control and population awareness of the condition are lower. Approximately 26% of Egyptian adults meet criteria for hypertension, but the prevalence of hypertension unawareness is unknown in this population. Here, we aim to assess prevalence and predictors of hypertension unawareness in Egyptian adults. Methods: We undertook a cross-sectional study using data from the 2015 Egyptian Health Issues Survey (EHIS). We included data from respondents aged 18-59 years. The outcome of interest was hypertension unawareness, defined by objectively measured blood pressure done during the EHIS survey and a self-reported unawareness of hypertension status. We used descriptive statistics and multivariable logistic regression for analysis. Findings: We analysed data from 2869 participants; 1915 of the respondents (65·5%) were in the 40-59 year age group, and 1639 respondents (56·5%) were women. More than half (56%) of EHIS respondents were unaware of their hypertension. The likelihood of hypertension unawareness was higher in participants aged 18-39 years than in those aged 40-59 years (odds ratio 1·91 [95% CI 1·48 −2·47]); men than in women (2·59 [1·85-3·62]; and never married compared with currently married participants (1·96 [1·19-3·24]). Compared with those who had college level education, hypertension unawareness was more likely in participants who had no education (2·21 [1·45-3·38], primary education (1·80 [1·20-2·70]), and secondary education (1·71 [1·21-2·40]). Additionally, hypertension unawareness was more likely in participants who had normal BMI than in those who were obese (1·82 [1·26-2·65]); and more likely in healthy participants than in those who had at least one chronic illness (4·53 [3·29-6·24]). Interpretation: More than half of Egyptian adults with hypertension are unaware of their condition. Those typically at lowest risk for hypertension appear to be at highest risk for hypertension unawareness. Younger, healthier, and less educated men are least likely to know of their hypertension. Our findings suggest the need for a targeted health education campaign and regular blood pressure screening in Egypt. Funding: None